SEXUAL AND REPRODUCTIVE BEHAVIOUR IN A CONTEXT OF EXTENDED ADOLESCENCE IN SRI LANKA - Boyagoda, K.; De Silva, W. I. (My University, 2012)
The changing demographic and socio-economic scenarios throughout the world have unfolded many important issues that demand the immediate focus of all relevant members of the world community. Among these, the sexual and reproductive health of the population is an important issue to that needs to be addressed immediately throughout the countries in the developing world where the quality of health has a major impact on the development process. The broad and comprehensive definition of reproductive health, adopted by the 1994 International Conference on Population and Development (ICPD) encompasses not merely women of childbearing age, but the reproductive health of all age groups of both sex. Nevertheless, more importantly, since the current generation of adolescents and youth constitute the immediate next generation of parents, their preparation for reproduction and sexuality has tremendous implications for their individual as well as national reproductive health outcomes. Thus the Programme of Action (PoA) developed and adopted by the ICPD highlighted the importance of “addressing the adolescent sexual and reproductive health issues, including unwanted pregnancy, unsafe abortion and sexually transmitted diseases, and HIV/AIDS, by promoting responsible and healthy reproductive and sexual practices, voluntary abstinence, and the provision of services and appropriate counseling specifically suitable for that age group” (United Nations, 1994). The entry into the reproductive phase of the lifecycle is an important threshold in a person’s life in which the choice and the behavioural patterns acquired during early adolescence will determine the subsequent life course (United Nations, 1989). Important steps in this transitional process are several critical life events such as puberty, initiation to sexuality, marriage and childbearing. The timing as well as the sequence and context in which these events take place have immediate and long-term repercussions for a particular individual’s sexual and reproductive health. Generally, the commencement of adolescence is associates with a period of rapid physical growth, in which a gradual development of the reproductive organs occurs along with the appearance of gender specific secondary sex characteristics and menarche in girls. In many countries of the developing region, due to generally low level of mortality and morbidity among children and adolescents, the overall well-being of this segment of the population has not been on the agenda for discussion among policy makers. In this decade, their issues and problems received priority mainly because of the strong advocacy by governments, individuals, organizations, and international agencies in the region (De Silva, 1998).